AKTOR KULTURAL DALAM PEMERINTAHAN TERENDAH DI SUMATERA BARAT (Posisi Ninik Mamak Dalam Struktural Adat dan Penyelenggaraan Pemerintahan Formal) - Yunus, Yasril (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2013)
This paper aims to propose the existence of the role of indigenous actors both as tribal stakeholders as well as administrators of the nagari (local administrative village) in West Sumatera, home to the Minangkabau people. This study used qualitative approach. Both internal aspects and external consideration of the adat (tradition) are analysed using SWOT by in-depth interview and focus group discussion of the tribal stakeholders as well as indigenous actors. The result shows that there are important role and leadership of the cultural actors in the governance of nagari who are capable of appreciating the values and rights of indigenous people without ignoring the values of modern democracy. Key words: cultural actors, governance of nagari, Minangkabau tradition